DIGITALISASI SISTEM INFORMASI AKUNTANSI PADA KINERJA DAN KEBERLANJUTAN UMKM DI INDONESIA - Dewi, Gita Apsari; Intan Wulandari, Anak Agung Ayu; Putu Diah Aryastuti Sanjiwani (Jurnal Akuntansi Kompetif, 2024)
The use of technology in producing accounting information is able to provide comprehensive changes to the evaluation of MSME performance. Digitalization of accounting information systems is applied by the MSME sector which seeks to simplify and speed up the decision-making process. MSMEs still have limited access to capital, access to markets and technology, so not all MSMEs implement accounting information systems. Weak human resource competence and supporting infrastructure also become obstacles to the implementation of accounting information systems. This research aims to provide an overview of the impact of accounting digitalization on the performance of MSMEs and the sustainability of the implementation of accounting digitalization in MSMEs. This research uses qualitative descriptive research with a literature study approach that examines relevant sources of information related to the implementation of digitalization of accounting information systems by MSMEs in Indonesia. AIS digitalization is able to have a positive effect on MSME performance through accurate financial information, increasing efficiency and reducing costs. In contrast to MSMEs which experience obstacles due to a lack of human resource capabilities and not understanding the importance of implementing AIS. Implementation of SIA can support the sustainability of MSMEs as seen from the various benefits obtained and their ability to compete in a competitive market.